2017
DOI: 10.1021/acs.jpcc.7b10748
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Evolution via the Bridging Inequivalent Dual-Site Reaction: First-Principles Study of a Quadruple-Perovskite Oxide Catalyst

Abstract: Perovskite-type oxides composed of earth-abundant elements have been extensively studied as possible candidates for oxygen evolution reaction (OER) catalysts. In our recent study, quadruple perovskite oxides (e.g., Ca-Cu 3 Fe 4 O 12 and LaMn 7 O 12 ) displayed catalytic activity that was higher than that of simple perovskites (e.g., LaMnO 3 ), but the reason has not yet been unveiled. We have conducted firstprinciples calculations of the several surface energies of LaMn 7 O 12 and adsorption energies of OER in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…At present, noble metal–based materials for OER, such as ruthenium oxides, are still ranking the highest level. [ 16,17 ] Meanwhile, nonnoble metal compounds, for instance, transition metal oxides, [ 18–21 ] perovskite, [ 22,23 ] hydroxide, [ 24,25 ] nitrides, [ 26,27 ] borates, [ 28,29 ] and so on, have also captured extensive interests for preparing high‐efficient OER catalysts. Among them, the metal fluoride, mostly literature reported for supercapacitor, lithium ion battery, etc., [ 30–33 ] is rarely wielded in the field of water electrolysis, possibly due to the chemical/electrochemical instability of fluoride ions and the weak bond between the metal ions and fluoride ions.…”
Section: Introductionmentioning
confidence: 99%
“…At present, noble metal–based materials for OER, such as ruthenium oxides, are still ranking the highest level. [ 16,17 ] Meanwhile, nonnoble metal compounds, for instance, transition metal oxides, [ 18–21 ] perovskite, [ 22,23 ] hydroxide, [ 24,25 ] nitrides, [ 26,27 ] borates, [ 28,29 ] and so on, have also captured extensive interests for preparing high‐efficient OER catalysts. Among them, the metal fluoride, mostly literature reported for supercapacitor, lithium ion battery, etc., [ 30–33 ] is rarely wielded in the field of water electrolysis, possibly due to the chemical/electrochemical instability of fluoride ions and the weak bond between the metal ions and fluoride ions.…”
Section: Introductionmentioning
confidence: 99%
“…Song and co-workersd esigned ah eterogeneousc atalyst with dual-metal sites, consisting of single Ni and Fe atoms embedded into g-C 3 N 4 units (Scheme 17 and Figure 7). [178] They found that oxygen evolution occurredt hrough the bridg-ing-inequivalent dual-site reaction, and OER adsorbates formed as trong chemical bond to the coordination-unsaturated octahedral site and aw eak chemical bond to ac oordination-saturated tetrahedral site or asquare-planar site (Figure 8). These dual-metal-site catalysts may offer an ew route to synthesize efficient WOCs.…”
Section: Dual-metal-site Wocsmentioning
confidence: 99%
“…In addition, Ikeno and co-workers investigated the higherO ER activity of the quadruple perovskite oxide LaMn 7 O 12 than that of the simple perovskite LaMnO through DFT computations. [178] They found that oxygen evolution occurredt hrough the bridg-ing-inequivalent dual-site reaction, and OER adsorbates formed as trong chemical bond to the coordination-unsaturated octahedral site and aw eak chemical bond to ac oordination-saturated tetrahedral site or asquare-planar site (Figure 8).…”
Section: Dual-metal-site Wocsmentioning
confidence: 99%
“…For instance, the strain of MO 6 octahedra in perovskite oxides varies the splitting of e g orbitals and impacts on the strength of metal–oxygen bonds to determine the oxygen evolution reaction (OER)/oxygen reduction reaction (ORR) activity . Also, some researchers found that distinct geometry coordination structure sites (distorted tetrahedral sites, or corner sharing of AO 4 and BO 5 sites) favorably adsorbed reaction intermediate species, which enhanced the activity of catalysts with those sites . Reports that elucidate the role of the local structure are limited to water oxidation or the ORR, the mechanisms of which have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Also, somer esearchersf ound that distinct geometry coordination structure sites (distorted tetrahedrals ites, or corner sharing of AO 4 and BO 5 sites) favorably adsorbed reactioni ntermediate species, whiche nhanced the activity of catalysts with those sites. [21,22] Reports that elucidate the role of the local structurea re limited to water oxidation or the ORR, the mechanisms of which have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%